"I never thought I would be an international speaker … but I am": an interpretive qualitative analysis of experiences of a project-based advocacy intervention. Issue 8 (14th September 2022) - Hoepner, Jerry K.; Yingst, Hannah; Harder, Bailey; Zehm, Crystal
ABSTRACT: Acquired brain injuries (ABI) result in changes to physical, cognitive, psychosocial, and economic domains, which alter an individual's sense of self and identity. Interactions with healthcare providers may further contribute to conceptualization of self after ABI. Cognitive rehabilitation is intended to address cognitive-communication impairments, as well as psychological changes to the sense of self and identity that follow ABI. The present investigation examined a project-based intervention, focused on advocacy. Participants developed a presentation for healthcare providers regarding consequences of ABI, strategies and supports necessary to successfully overcome daily challenges, and insights into the lived experience. Ten individuals with chronic ABI participated in one of three roles (presenter, video contributor, or content developer). Written interviews allowed participants to generate and refine their responses. Interpretive Description qualitative analyses was used to examine interviews. Iterative analysis identified five themes across all participant roles: renewed sense of self, positive impact on providers to care of future individuals with brain injurie s, rewarding and humbling, being heard, and alternate personal narratives and identitie s. The remaining theme applied only to presenters, improved clarity and conciseness . Group, project-based interventions have the potential to positively influence sense of self in combination with narrative therapy techniques in the chronic phase of recovery.